Two solvent-dependent porous coordination polymers with –OH decorated ligands: unusual non-crystallographic net and fsh topology1. Issue 30 (14th August 2015) - Duan, Jingui; Higuchi, Masakazu; Zou, Changchang; Jin, Wanqin; Kitagawa, Susumu
<x xml:space="preserve">Abstract</x> The variable architectures of two new porous coordination polymers, controlled by solvent system, exhibit a structural progression from an unusual non-crystallographic net to a (4, 6)-connected framework with fsh topology.